2007
DOI: 10.1080/00048670601172772
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated with Incident Mental Health Disorders After Stroke

Abstract: Approximately 1 in 3 patients develop a mental health disorder after stroke, although incidence estimates are relatively low. Post-stroke psychosis is associated with greater 10-year mortality, but the mechanisms underlying such an association are yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 23 publications
3
60
0
1
Order By: Relevance
“…This prevalence is higher than prevalence of 9.1% reported by Williams et al 37 , similar to 36.6% reported by Almeida et al 38 , but lower than 49-54.7% reported by other researchers [39][40] . All the other reports were from the developed countries.…”
Section: Discussionsupporting
confidence: 56%
“…This prevalence is higher than prevalence of 9.1% reported by Williams et al 37 , similar to 36.6% reported by Almeida et al 38 , but lower than 49-54.7% reported by other researchers [39][40] . All the other reports were from the developed countries.…”
Section: Discussionsupporting
confidence: 56%
“…These included 134 outpatients with either schizophrenia (N ¼ 80, comprised of 61% women) or schizoaffective disorder (N ¼ 54, comprised of 48% women), and 123 HCs (comprised of 48% women) with no history of major neuropsychiatric illness. All the subjects were recruited from the greater San Diego community and interviewed using the Structured Clinical Interview for the DSM-IV-TR (SCID) (Almeida and Xiao, 2007). Subjects were excluded if they had 1) other current DSM-IV-TR Axis I diagnoses; 2) alcohol or other substance (other than tobacco) abuse or dependence within 3 months prior to enrollment; 3) diagnosis of dementia, mental retardation, or a major neurological disorder; 4) or any medical disability that interfered with their ability to complete the study assessments.…”
Section: Study Participantsmentioning
confidence: 99%
“…Two hospital-registry studies identified only 0.4% 96 and 3.1% 97 of stroke patients with a psychotic disorder. The incidence was 1.11 per 1000 person-years, with gradual onset at an average of 6.1 months after stroke.…”
Section: Psychosis and Psychotic Symptomsmentioning
confidence: 99%
“…The incidence was 1.11 per 1000 person-years, with gradual onset at an average of 6.1 months after stroke. 97 Single psychotic symptoms not fulfilling criteria for syndromal psychotic disorder appear more common. For example, among patients admitted to somatic or rehabilitation wards of Dutch nursing homes, delusional symptoms were present in 3-10% of patients 68,77 and hallucinations in about 4%.…”
Section: Psychosis and Psychotic Symptomsmentioning
confidence: 99%
See 1 more Smart Citation